The So-Called “Islamic Terrorism”: A Tale of the Ambiguous Terminology - Dwi Surya Atmaja (Al-Albab, 2016)
"What does the term "terrorism" mean." Why does the term “terrorism” often identified as Islam? "If terrorism is an ism that affects "terror" that it generates, while Islam which literally means "peace", then the two terms certainly mismatch! Such question and statement show Muslims’ concern over frequent phenomena of "terrorism" using Islamic religious symbols. The research undertaken proved that there are three explanations. First, a close tripartite network connection between “terrorism experts” and the circles of power policy holders who are also supported by senior journalists in the international media influence. Second, a long tradition of Orientalist studies in the study of the Middle East region and the study of religion in the Arab culture. Figures such as Bernard Lewis, Noah Feldman, Raphael Patai and other Middle East experts often sit with other experts in the field of terrorism (the first factor) and become main advisors and expert staff for the US government in the formulation of action to counter terror. It was the catalyst for the transmission of viewpoint which then decorated orientalist discourse of Islamic terrorism in the process of political policies. Third, a lot of Islamic terrorism discourse refers to the long tradition of cultural stereotypes and biased representations of the media that often portray Islam and Muslims as ‘the enemy’. The reason is that it reflects the perspective of socio-Western culture that fears and worries the other oriental parties which has been stereotyped since the imperial era. Many also argue that the dichotomy of the orientalist views are deliberately preserved as a form of new style imperialism